جزاء الكفار والمشركيـن في الدنيا في ضوء القرآن الكريم: دراسة بلاغية ........................................................ The Punishment of Infidels in This World in the Light of the the Holy Quran: A Rhetorical Study - عنبرين فريال (الدراسات الإسلامية, 2019)
This research paper focused on the rhetorical study of select verses of the holy Quran about the punishment of infidels in this world. The holy Quran explains the punishment of the deniers of Islam in this world as well as in the world hereafter. Basically these deniers are divided in three main categories. The first category is called infidels or polytheists; the second one is known as Ahl al-Kitab (Jews and Christians); and the third category is hypocrites. I have discussed the punishment of infidels in this world in this research work. This work is based on the analytical approach. I have attempted to address the questions concerning the punishment of disbelievers and polytheists because of their intellectual and practical situations. I also highlighted rhetorical significance of the words, structures, and sentences used for this purpose in the holy Quran. Furthermore, the study has been divided into two basic aspects of the punishment. The first concerns with the internal spiritual disorders of an infidel, and the second explains external spiritual and assessable matters in this regard. Keywords: rhetorics, infidels, punishment, polytheists, the Quran.